Body Image Coping Strategies as Mediator between Physical Appearance Related Teasing and Body Esteem among Adolescents - Adeymend Reny Japil; Mazni Mustapha; Guan, Teik Ee (2018)
This study was conducted to investigate the mediation effect of coping strategies in the relationship between physical appearance-related teasing and body esteem among adolescents. In total, 363 adolescents (179 males and 184 females) aged 16-year-old participated in the study. Physical Appearance-Related Teasing Scale – Revised, Body Esteem Scale for Adolescents and Adults, and Body Image Coping Strategies Inventory were used to collect quantitative data on respondents’ experiences concerning physical appearance-related teasing, body esteem, and coping strategies about body image. Multiple regression analyses using bootstrapping procedures showed positive rational acceptance partially mediated the relationship between all physical appearance-related teasing dimensions (form of harassment, appearance-related teasing, and physical-related teasing) and body esteem – appearance and attribution, partially mediated the relationship between form of harassment and body esteem – weight, and fully mediated the relationship between appearance and physical-related teasing and body esteem – weight. Appearance fixing were also partially mediated the relationship between form of harassment and appearance related teasing and body esteem – appearance and fully mediated the relationship between physical-related teasing and body esteem – appearance. Appearance fixing were found to partially mediate the relationship between all physical appearance-related teasing dimensions and body esteem –attribution. There is no mediation effects of appearance fixing in the relationship between all physical appearance-related teasing dimensions and body esteem – weight. Analyses also found that avoidance partially mediated the relationship between all physical appearance-related teasing dimensions and body esteem – appearance, and the relationship between both form of harassment and appearance-related teasing and body esteem – weight. Meanwhile, there is no mediation effects of avoidance in the relationship between physical-related teasing and body esteem – weight, and the relationship between all physical appearance-related teasing dimensions and body esteem – attribution. This information is useful for the planning of health programs as well as intervention and prevention programs to control and combat physical appearance-related teasing and body satisfaction problems among adolescents.